Effects of linagliptin on morphine dependence in larval zebrafish (Danio rerio) - Lupina, Malgorzata; Listos, Joanna (Current Issues in Pharmacy and Medical Sciences, 2022)
Drug addiction is a chronic, recurrent disease of the central nervous system that leads to the development of comorbidities and premature death. Despite extensive scientific research concerning addiction, no effective method of addiction pharmacotherapy has been known so far. Glucagon-like peptide 1 has been suggested to play a role in the rewarding effect of addictive drugs. Linagliptin is a selective dipeptidyl peptidase-4 inhibitor that suppresses the rapid degradation of endogenous glucagon-like peptide-1. In clinical practice, it is used as an antidiabetic drug, but recent studies have confirmed its role in the activity of the central nervous system. This pilot study was conducted to ascertain whether linagliptin might influence morphine dependence – a locomotor activity test was carried out to assess the intensity of morphine withdrawal symptom. The obtained results clearly confirmed that linagliptin (0.01 and 0.1 mM) reduced the locomotor activity in morphine-dependent larval zebrafish. The undertaken experiments clearly indicates that linagliptin is involved in the addictive effects of morphine, thus, further studies on higher organisms should be carried out.